(untitled) - General A Silver (Reading, Massachusetts, 1989)
This book provides a comprehensive overview to systems analysis with emphasis on information management and hands-on applications. The book has a balanced presentation to both theoretical and applied aspects of systems analysis, introducing state-of-the-art methodology ans systems procedures. It also covers modern software and hardware concepts, computer-assisted software engineering (CASE), and automated systems analysis tools
Keywords: management information,systems analysis,systems design